Didactic sequel proposal involving a high school podcast production: reflections on contemporary aspects of labor - Neves, Ana Clara Martins; Araújo, Claudia Patrocínio de; Moreira, Tatiana Aparecida (The ESPecialist, 2025)
This article proposes reflections on the application of a didactic sequence developed in accordance with Dolz, Noverraz, and Schneuwly (2011) addressing contemporary issues related to labor, diversity, and power relations. The didactic sequence referred aimed primarily to develop oral skills in Portuguese language classes through the production of a podcast program. Initial discussions on the theme were guided by the analysis of Brazilian artistic works: the song A Vida é Desafio (2002) by Racionais MC’s, the paintings Trabalhadores (1938) and Operários (1933) by Tarsila do Amaral, and the artwork Invisíveis (2023) by JV Abreu. The theoretical framework included: Bakhtin’s concepts of dialogical relations and the responsive-active atitude (Bakhtin, 1997; 2016); Marcuschi’s speech-writing continuum (Marcuschi, 2008); and Foucault’s analysis of power relations (Foucault, 1995). The results demonstrated that students successfully produced a podcast script, highlighting the speaking-writing continuum as they translated their analysis of the artworks into oral discourse. The activity also fostered critical reflection on contemporary labor issues, revealing students’ exercise of citizenship, critical thinking, while also showcasing their ability to express themselves fluently and articulately. Thus, this didactic sequence emerges as a valuable pedagogical approach to address current themes (highlighting oral communication), an often underrepresented skill in high school education.